Foot care intervention delivered by community health worker (CHWs): A scoping review - Okatiranti Okatiranti; Desy Nuryunarsih; Richard Windle; Sarah Goldberg (Taylor & Francis Group, 2024)
ABSTRACTVariations of Community Health Workers (CHWs) interventions in diabetes self-management education (DSME) have been reviewed by many studies. In contrast, specific interventions regarding foot care intervention (FCI) are scarce and need to be explored further as one preventive measure to reduce diabetic foot problems in the community. This scoping review aimed to identify, and report nature of FCIs and the core components of FCIs delivered by CHWs. The scoping review was undertaken using PRISMA Extension for Scoping Reviews (PRISMA-ScR). The following electronic databases were searched for articles from data first indicated date through December 2022: CINAHL, EMBASE, Cochrane, Scopus, Web of Science, Theses ProQuest, PubMed, google scholar and other sources by using search terms related to foot care, community health workers, and diabetes mellitus. Descriptive synthesis was used to summarise the data. Nine studies from 1644 were included. All studies found that CHWs provided DSME in general, and foot care education was included. There was no detailed description of the core components of the intervention on foot care. Although, all studies might not provide detailed data on how CHW provided FCIs; the CHW intervention is an undoubtedly vital strategy to promote and prevent foot problems in medically underserved communities.